2015
DOI: 10.1002/jso.23995
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of high‐risk stage I and II colon tumors based on evaluation of CAV1 gene expression

Abstract: Evaluation of CAV1 expression offers valuable prognostic information for patients with colorectal cancer, and could be used to select patients with stage I or II disease, who are at increased risk of unfavorable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
5
0
1
Order By: Relevance
“…Although its role in metastasis formation is controversially discussed [ 55 ], there is evidence that CAV1 is decreased in early stages of carcinogenesis [ 56 , 57 ], but is found to be elevated at later stages [ 58 ], including in CRC [ 59 ]. Moreover, increased CAV1 expression in T4-stage CRCs was associated with increased invasiveness [ 60 ], and depletion of CAV1 reduced the invasive properties of human CRC cell lines [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although its role in metastasis formation is controversially discussed [ 55 ], there is evidence that CAV1 is decreased in early stages of carcinogenesis [ 56 , 57 ], but is found to be elevated at later stages [ 58 ], including in CRC [ 59 ]. Moreover, increased CAV1 expression in T4-stage CRCs was associated with increased invasiveness [ 60 ], and depletion of CAV1 reduced the invasive properties of human CRC cell lines [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Caveolin-1 can both activate and inhibit the activity of the receptors (47,48). Accordingly, in some types of cancer Caveolin-1 was characterized as an oncosuppressor (breast cancer (49)), and in others as an oncogene (colorectal and prostate cancer (50,51)). Controversial data were also obtained for GBM, where in some experimental models…”
Section: Discussionmentioning
confidence: 99%
“…In fact, this hypothesis is supported by the reported role of CAV‐1 promoting cell invasion and metastasis of CRC cells [14, 15]. Moreover, it has been recently reported that CAV‐1 determines unfavorable outcome in stage I–II CRC and was found associated with tumor with greater depths of invasiveness [16]. Thus, the precise status of CAV‐1 in CRC must be fully clarified due to discrepancies in the existing literature.…”
Section: Introductionmentioning
confidence: 93%